Development of enhanced hypericin yielding transgenic plants and somaclones: high throughput direct organogenesis from leaf and callus explants of Hypericum perforatum - Khan, Shamshad A.; Verma, Priyanka; Arbat, Akshata; Gaikwad, Sushma; Parasharami, Varsha A. (Industrial Crops and Products, 2018)
Hypericum perforatum is well known for its anti-depressent properties due to the presence of hypericins and hyperforins. The direct regeneration protocol from leaf explants and Agrobacterium tumefaciens mediated genetic transformation is a prerequisite for gene transfer studies in this valuable plant system as H. perforatum has shown its recalcitrance to these studies previously. The aim of generating transgenic shoots or somaclones in the present study is to select high hypericine yielding H. perforatum plants. High throughput direct bud organogenesis from leaf explants has been achieved for the first time in this plant system on media combination of MS + 5.0 mg/l BAP + 1.0 mg/l. This medium interestingly also worked as the indirect regeneration media for generation of somaclones from callus cultures. Thus far optimized single media can be used for direct and indirect regeneration in H. perforatum. The direct regeneration frequency of plantlets from leaf explants was found to be 80% while 100% was the regeneration frequency noted for indirect plantlet regeneration from callus cultures. The optimized direct regeneration protocol from leaf explants was utilized for A. tumefaciens (harbouring pCAMBIA 1301) mediated genetic transformation studies with the aim of establishing transgenic lines of H. perforatum. The resultant study successfully gave rise to kanamycin resistant GUS positive shoots with transformation efficiency of 3136 +/- 3.6. A total of four transgenic H. perforatum clones namely T2, T3, T5 and T8 with different growth parameters were established, where highest of fivefold increase in hypericin content was recorded by T5 (276.8 +/- 9.2 mu g/g dry wt.) in comparison to control non transformed plants (35.6 +/- 2.7 mu g/g dry wt.). Interestingly the presence of serotonin and melatonin was also detected in transgenic plants on TLC basis. The transgenic nature of the plants was confirmed by PCR with amplification of uidA gene. Apart from it, from indirect regeneration from callus, total of ten somaclones were generated. The ISSR profiling of somaclones scored a total of 156 bands, among which 118 were polymorphic in nature. The glasshouse established soma clones showed up to twofold increase in hypericin content on HPLC analysis.
Keywords: Direct regeneration; Hypericin; Hypericum perforation; Indirect regeneration; ISSR; Somaclones; Transgenic plants